Quantum dots for memory applications. Issue 8 (8th July 2013) - Dimitrakis, P.; Normand, P.; Ioannou‐Sougleridis, V.; Bonafos, C.; Schamm‐Chardon, S.; BenAssayag, G.; Iliopoulos, E.
<x xml:space="preserve">Abstract</x> In this paper, we review the fabrication and the electrical characteristics of metal–insulator–semiconductor (MIS) devices with semiconductor quantum dots (QD) embedded into the gate dielectric. Our results originate from experiments performed the last decade and cover Si QDs realized by low‐energy ion‐beam synthesis (IBS) as well as GaN QDs formed by molecular beam deposition (MBD). Besides the basic capacitance‐to‐voltage (C–V) and current‐to‐voltage (I–V) characterization, the memory properties of the fabricated MIS devices were investigated in terms of memory window under pulse operation and charge retention. The optimization of Si‐QD memory cells is reviewed and a methodology for both the extraction of various device parameters and the identification of mechanisms governing the charge loss process are presented. GaN QDs, which exhibit negative conduction band‐offset with respect to the Si conduction band, offer an interesting alternative to Si QDs as discussed herein based on our investigations of GaN‐QD capacitors fabricated by a complementary‐metal‐oxide‐semiconductor (CMOS) compatible process.